2010
DOI: 10.1530/eje-10-0465
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of acromegaly in a highly polluted area

Abstract: Objective: Despite the contribution of national registries and population-based reports, data concerning the epidemiology of acromegaly is scanty. In addition, the role of the environmental context has not been investigated. Design: Epidemiology of acromegaly was studied in the province of Messina (Sicily, Italy), focusing on the influence of environmental factors. Methods: Four zones, characterized by different degrees of exposition to environmental toxins due to industrial pollution, were identified in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 14 publications
2
38
0
4
Order By: Relevance
“…The authors postulated that the overrepresentation of women may be due to a late presentation related to economic and social factors in their country. However, the relatively young age of their patients (ranging from 17 to 50 years) compared with the whole series (median age at diagnosis 44 years) does not support this hypothesis and an impact of environmental (30) or genetic factors (31,32) cannot be ruled out. In our series, only one patient was found to have MEN1 while other patients had no family history of pituitary adenoma nor hypercalcaemia and/or MEN1-associated lesions.…”
Section: European Journal Of Endocrinologymentioning
confidence: 86%
“…The authors postulated that the overrepresentation of women may be due to a late presentation related to economic and social factors in their country. However, the relatively young age of their patients (ranging from 17 to 50 years) compared with the whole series (median age at diagnosis 44 years) does not support this hypothesis and an impact of environmental (30) or genetic factors (31,32) cannot be ruled out. In our series, only one patient was found to have MEN1 while other patients had no family history of pituitary adenoma nor hypercalcaemia and/or MEN1-associated lesions.…”
Section: European Journal Of Endocrinologymentioning
confidence: 86%
“…Most are sporadic, slow-growing and diagnosed in middle-aged to older individuals [35]. Epidemiological studies are few but recent reports of increased prevalence of pituitary adenomas in high industrialized areas [19] and, possibly, after toxic spillage [20] suggested a link to environmental causes.…”
Section: Discussionmentioning
confidence: 99%
“…Further, in vivo models revealed a higher incidence of pituitary adenomas in rats treated with a mixture of endocrine disruptors [18]. In humans, epidemiological studies showed an increased prevalence of growth hormone (GH)-secreting pituitary tumors in high industrial density areas [19] and, possibly, higher incidence of pituitary neoplasia following the accidental spillage of dioxin [20]. An additional link between endocrine disruptors and pituitary tumorigenesis was provided by the discovery of mutations in the aryl hydrocarbon receptor interacting protein ( AIP ) gene in patients with pituitary tumors [21], as the aryl hydrocarbon receptor (AhR) is well-known to bind toxins and phytochemicals [22].…”
Section: Introductionmentioning
confidence: 99%
“…Much higher frequencies of pituitary adenomas with positive immunohistochemistry for GH has been observed in autopsies of patients without known pituitary disease [2][3][4][5]. In population studies, Daly et al [6] identified nine cases of acromegaly in a population of 71,972 inhabitants (prevalence of 125/1,000,000), and Cannavò et al [7] identified 28 cases in an area with 243,381 inhabitants (prevalence of 115/1,000,000) and 10 cases in another population of 47,554 inhabitants (prevalence of 210/1,000,000), with both populations being exposed to high industrial pollution [7]. Schneider et al [8] measured serum IGF-1 in 6,773 adult primary care patients and biochemical acromegaly was diagnosed in six patients (prevalence of 886/1,000,000), with the observation of an exuberant phenotype and pituitary adenoma confirmed by MRI in at least two (prevalence of 295/1,000,000).…”
Section: Introductionmentioning
confidence: 99%